Can Board Gender Diversity Strengthen ESG’s Role in Preventing Financial Fraud in ASEAN-5? - Fairuz Fairuz; Rofikoh Rokhim (Green Publisher Indonesia, 2025)
This study focuses on analyzing the effect of Environmental, Social, and Governance (ESG) performance on financial fraud indication probability in publicly listed companies in ASEAN-5 Countries, with board gender diversity as a moderating variable. This research utilizes panel data from ASEAN-5 non-financial listed companies during the period of 2019-2023, and applies logistic regression methods to test the hypotheses, using The Beneish M-Score to assess the level of financial statement fraud. Our results shows that higher ESG score can reduce the probability of financial fraud significantly, while the female board prove to strenghthen the negative impact between ESG performance and Financial Fraud, also intensify the performance of E and G in inhibiting the probability of financial fraud indication. Furthermore, this paper provides new insights into how ESG performance can contribute to reducing financial fraud, with the moderation of board gender diversity. Also, by developing and enforcing the regulation regarding corporate governance and information disclosure, regulators and policy makers can mitigate the risk of financial fraud in ASEAN-5 country.